A roadmap to integrating resilience into the practice of coral reef restoration. (19th May 2022) - Shaver, Elizabeth C.; McLeod, Elizabeth; Hein, Margaux Y.; Palumbi, Stephen R.; Quigley, Kate; Vardi, Tali; Mumby, Peter J.; Smith, David; Montoya‐Maya, Phanor; Muller, Erinn M.; Banaszak, Anastazia T.; McLeod, Ian M.; et al.
Abstract: Recent warm temperatures driven by climate change have caused mass coral bleaching and mortality across the world, prompting managers, policymakers, and conservation practitioners to embrace restoration as a strategy to sustain coral reefs. Despite a proliferation of new coral reef restoration efforts globally and increasing scientific recognition and research on interventions aimed at supporting reef resilience to climate impacts, few restoration programs are currently incorporating climate change and resilience in project design. As climate change will continue to degrade coral reefs for decades to come, guidance is needed to support managers and restoration practitioners to conduct restoration that promotes resilience through enhanced coral reef recovery, resistance, and adaptation. Here, we address this critical implementation gap by providing recommendations that integrate resilience principles into restoration design and practice, including for project planning and design, coral selection, site selection, and broader ecosystem context. We also discuss future opportunities to improve restoration methods to support enhanced outcomes for coral reefs in response to climate change. As coral reefs are one of the most vulnerable ecosystems to climate change, interventions that enhance reef resilience will help to ensure restoration efforts have a greater chance of success in a warming world. They are also more likely to provide essential contributions to global targets to protect natural biodiversity and the human communities that rely on reefs. Abstract : Coral reefs are one of the most vulnerable ecosystems to climate change, and scientists have increasingly called for restoration interventions to be used to increase coral reef resilience to climate change. However, recent global reviews highlight a critical gap in implementation in the design and practice of restoration programs. We review the current literature and provide recommendations that integrate resilience principles into restoration design and practice for project planning and design, coral selection, site selection, and broader ecosystem context. We also discuss future opportunities to improve restoration methods to support enhanced outcomes for coral reefs in response to climate change.